Age-related hearing loss is associated with alterations in temporal envelope processing in different neural generators along the auditory pathway - Farahani, Ehsan Darestani; Wouters, Jan; van Wieringen, Astrid (Frontiers in Neurology, 2022)
People with age-related hearing loss suffer from speech understanding difficulties, even after correcting for differences in hearing audibility. These problems are not only attributed to deficits in audibility but are also associated with changes in central temporal processing. The goal of this study is to obtain an understanding of potential alterations in temporal envelope processing for middle-aged and older persons with and without hearing impairment. The time-series of activity of subcortical and cortical neural generators was reconstructed using a minimum-norm imaging technique. This novel technique allows for reconstructing a wide range of neural generators with minimal prior assumptions regarding the number and location of the generators. Results indicated that the response strength and phase coherence of middle-aged participants with hearing impairment (HI) were larger than for normal hearing (NH) ones. In contrast, for the older participants, a significantly smaller response strength and phase coherence were observed in the participants with HI than the NH ones for most modulation frequencies. Hemispheric asymmetry in the response strength was also altered in middle-aged and older participants with hearing impairment and showed asymmetry toward the right hemisphere. Our brain source analyses show that age-related hearing loss is accompanied by changes in the temporal envelope processing, although the nature of these changes vary with age.